Sokol between making nation and state - Pavlin, Tomaž; Čustonja, Zrinko (2018)
The Sokol gymnastic movement was an important part of civil societies of Slavic nations. The first Sokol society within Yugoslavian nations (Slovenes, Croats, Serbs) was founded in 1863 in Ljubljana and in a few decades, it spread throughout the Slovene, Croatian, and Serbian territories. In the Austro-Hungarian period before WWI, Sokol valued itself as a national, liberal and emancipation-seeking movement, based on the Tyrsch’s gymnastics and national and pan-Slavic idea. In 1919, following the end of WWI and with the formation of the Yugoslav state, the national Sokol organisations merged in the centralised Yugoslav Sokol Union. The Yugoslavian state went through difficult political situations and confrontations in the first decade, which culminated in the summer of 1928 with shooting in the parliament in Belgrade. In attempting to solve the situation, King Aleksandar Karadjordjević proclaimed the so-called Sixth January Dictatorship (1929). Consequently, the government, with the approval of the King, adopted, on the 4th of December 1929, the law on establishing of a new all-state gymnastic organisation Sokol of the Kingdom of Yugoslavia. The new Sokol organisation, based on the Sokolism of the former Yugoslav Sokol (Sokol’s gymnastics, principles, national-liberal and Slavic idea) was constituted at the beginning of 1930. It was supported by the King and government and the King’s son, Prince Petar became the leader of the Sokol organisation. After the assassination of king Aleksandar (1934), in the filling-in period of Prince Pavle (1935-41) and government of the Prime Minister Milan Stojadinović (1935-39), Sokol of the Kingdom of Yugoslavia fell out of political grace in the western Roman-Catholic regions and it had to defend its position.
Bibliografija: str. 267-268.
Keywords: Gimnastika -- Sokolski pokret -- Hrvati -- Slovenci -- Srbi; Zagrebačko tjelovježbeno društvo "Hrvatski sokol"; Kraljevina Jugoslavija -- Austro-Ugarska